1992
DOI: 10.1302/0301-620x.74b4.1624505
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, clinical and radiological aspects of osteopoikilosis

Abstract: Osteopoikiosis is a rare condition showing characteristic sclerotic lesions on radiographic examination, which are diagnostic for the frait. We report four patients presenting with various complaints and 49 members of their families who later were found to have osteopoikilosis. The mean age of all 53 was 27.5 years and the male:female ratio was 33:20. Most had lesions in the small tubular bones. We studied the epidemiological, clinical and radiological features ofthese patients and from the pedigrees conclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
11

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 5 publications
2
74
0
11
Order By: Relevance
“…3,4 In an epidemiological study of familial Osteopoikilosis by Benli et al a predominance of these lesions was found in the phalanges of hand (100%) followed by carpal bones (97.4%), metacarpals (92.3%), foot phalanges (87.2%), metatarsals (84.4%), tarsal bones (84.6%), pelvis (74.4%), radius (66.7%), ulna (66.7%), sacrum (58.9%), humerus (28.2%), tibia (20.5%) and fibula (12.8%). 5 On serial radiographs these sclerotic may show an increase or decrease in size or number with occasional disappearance in children, in sharp contrast with adults in whom these lesions remain more or less static. 1 Differential considerations for this abnormality include osteoblastic metastases, tuberous sclerosis and mastocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In an epidemiological study of familial Osteopoikilosis by Benli et al a predominance of these lesions was found in the phalanges of hand (100%) followed by carpal bones (97.4%), metacarpals (92.3%), foot phalanges (87.2%), metatarsals (84.4%), tarsal bones (84.6%), pelvis (74.4%), radius (66.7%), ulna (66.7%), sacrum (58.9%), humerus (28.2%), tibia (20.5%) and fibula (12.8%). 5 On serial radiographs these sclerotic may show an increase or decrease in size or number with occasional disappearance in children, in sharp contrast with adults in whom these lesions remain more or less static. 1 Differential considerations for this abnormality include osteoblastic metastases, tuberous sclerosis and mastocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…O estudo com radiofármacos específi-cos para osso não mostra atividade aumentada nas áreas com as alterações ósseas (4) . Histologicamente, as áreas escleróticas são condensações focais de osso compacto lamelar dentro da esponjosa (1) . Os achados microscópicos das lesões são idênti-cos aos encontrados nas ilhotas ósseas.…”
Section: Discussionunclassified
“…A osteopoiquilose é uma displasia osteosclerótica, assintomática, também conhecida como osteopatia condensante disseminada ou doença do osso manchado (1) . Descrita no início do século por Stieda, Albers-Schönberg e Ledoux-Lebard, costuma ser um achado radiológico em investigação de doença concomitante (2) .…”
Section: Introductionunclassified
“…Osteopoikilosis exists in hereditary (autosomal dominant transmission) and sporadic forms [4][5][6][7] and is one of several bone dysplasias characterized by defective endochondral bone formation.…”
Section: 3mentioning
confidence: 99%
“…2 The lesions have been described in all age groups, and although prevalence studies have shown a higher frequency among men, the apparently unequal sex distribution may be a result of referral bias in the literature (men are more likely than women to present to hospital with traumatic injuries requiring radiologic investigation). 2,3 Osteopoikilosis exists in hereditary (autosomal dominant transmission) and sporadic forms [4][5][6][7] and is one of several bone dysplasias characterized by defective endochondral bone formation. 5 Endochondral ossification refers to the formation of the long and flat bones, which begins from a primitive hyaline cartilaginous model.…”
mentioning
confidence: 99%